(untitled) (Conferencea, 2023)
Georgia and the Georgian nation have always represented and are a copy of the constituent part of humanity, which is more or less subject to the regularities of its development and depends on it to a significant extent. Architecture in Georgian is architecture, which is a function of the needs of the population. The needs change according to population growth, development of science and technology, economic opportunities, natural features and other objective and subjective conditions.